Education Financing Management Strategy in Improving Facilities and Infrastructure at SMP Nu Al Islami Pesanggaran - Sharifudin, Khabib; Ekaningsih, Lely Ana Ferawati (SAINTIS Publishing, 2024)
This study aims to formulate an effective and efficient education financing management strategy in improving the quality of facilities and infrastructure at SMP NU Al Islami Pesanggaran. With a qualitative approach and descriptive design, this study explores the social, cultural, and economic conditions of schools through in-depth interviews, participatory observations, and documentation studies. The data were analyzed using the thematic analysis method with triangulation to ensure the credibility of the results. Research at SMP NU Al Islami Pesanggaran highlights three important aspects in education management 1. The strategic role of the school committee as a mediator to increase community participation. 2. Suboptimal financial management due to lack of planning and technology. 3. As well as partnerships with external parties that have not been utilized to the fullest. Strengthening communication and management capacity is needed to optimize the role of school committees. Financial management solutions include training and implementation of modern systems. External partnerships can be strengthened with better communication strategies.